Nor-24-homoscalaranes, Neutrophilic Inflammatory Mediators from the Marine Sponge Lendenfeldia sp. - Bo-Rong Peng; Li-Guo Zheng; Lo-Yun Chen; Mohamed El-Shazly; Tsong-Long Hwang; Jui-Hsin Su; Mei-Hsien Lee; Kuei-Hung Lai; Ping-Jyun Sung (Pharmaceuticals, 2023)
The marine sponge Lendenfeldia sp., collected from the Southern waters of Taiwan, was subjected to chemical composition screening, resulting in the isolation of four new 24-homoscalarane compounds, namely lendenfeldaranes R–U (1–4). The structures and relative stereochemistry of the new metabolites 1–4 were assigned based on NMR studies. The absolute configurations of compounds 1–4 were determined by comparing the calculated and experimental values of specific optical rotation. The antioxidant and anti-inflammatory activities of the isolated compounds were assayed using superoxide anion generation and elastase release assays. These assays are used to determine neutrophilic inflammatory responses of respiratory burst and degranulation. Compounds 2 and 4 inhibited superoxide anion generation by human neutrophils in response to formyl-L-methionyl-L-leucyl-L-phenylalanine/cytochalasin B (fMLP/CB) with IC50: 3.98–4.46 μM. Compounds 2 and 4 inhibited fMLP/CB-induced elastase release, with IC50 values ranging from 4.73 to 5.24 μM. These findings suggested that these new 24-homoscalarane compounds possess unique structures and potential anti-inflammatory activity.